Growth rates of Brazilian carbonate speleothems by the 210Pb chronological method - Figols, André P. [UNESP]; Bonotto, Daniel M. [UNESP] (Springer Nature, 2024)
Carbonate speleothems contain measurable concentration of 210Pb, which can be used to estimate modern growth rates up to a 150-years timescale. However, data referring to such application of this geochronological method are scarce in the Southern Hemisphere, with most studies based on temperate climate locations in the Asian continent. Such a lack of data makes it difficult to approach an investigative comparison of the main physical parameters that influence the precipitation rate of calcium carbonate in caves. In this context, the present study describes the record of longitudinal growth rates of carbonate speleothems sampled in two different Brazilian regions: Pains municipality (Midwestern Minas Gerais State) and Curitiba Metropolitan Area (CMA, eastern Paraná State), whose climates are subtropical with dry winter (Cwa) and wet temperate (Cfb), respectively. Segments of variable thickness from eight stalactites samples were subjected to HCl dissolution, 210Po deposition onto copper discs, and 210Po analysis by alpha spectrometry for yielding the activity concentration data. 210Po activity concentration data provided the 210Pb values due to radioactive equilibrium condition between these radionuclides. Although all samples exhibited a quantifiable measure of the 210Pb activity concentration in their sectional layers, the longitudinal growth rate could not be estimated by the CF:CS method for three of the eight stalactites. However, the modified CRS method allowed determine growth rates for all speleothems. The mean 210Pb CRS growth rate obtained at Pains and CMA sites is 1.4 ± 0.1 mm/year and 1.5 ± 0.2 mm/year, respectively, indicating coincidence at both sites and suggesting that the approach is reliable for determining modern growth rates.
Keywords: 210Pb dating; Carbonate speleothems; Growth rates; Limestone caves; Minas Gerais and Paraná States in Brazil